Bio-inspired vertebral design for scalable and flexible perovskite solar cells - Meng, Xiangchuan; Cai, Zheren; Zhang, Yanyan; Hu, Xiaotian; Xing, Zhi; Huang, Zengqi; Huang, Zhandong; Cui, Yongjie; Hu, Ting; Su, Meng; Liao, Xunfan; Zhang, Lin; et al. (Nature communications, 2020)
The translation of unparalleled efficiency from the lab-scale devices to practical-scale flexible modules affords a huge performance loss for flexible perovskite solar cells (PSCs). The degradation is attributed to the brittleness and discrepancy of perovskite crystal growth upon different substrates. Inspired by robust crystallization and flexible structure of vertebrae, herein, we employ a conductive and glued polymer between indium tin oxide and perovskite layers, which simultaneously facilitates oriented crystallization of perovskite and sticks the devices. With the results of experimental characterizations and theoretical simulations, this bionic interface layer accurately controls the crystallization and acts as an adhesive. The flexible PSCs achieve the power conversion efficiencies of 19.87% and 17.55% at effective areas of 1.01 cm 2 and 31.20 cm 2 respectively, retaining over 85% of original efficiency after 7000 narrow bending cycles with negligible angular dependence. Finally, the modules are assembled into a wearable solar-power source, enabling the upscaling of flexible electronics. Flexible perovskite solar cells suffer huge efficiency loss upon area scale-up due to brittleness of ITO and poor perovskite film quality. Here Meng et al. solve this by inserting a conductive and glued polymer layer between ITO and perovskite layers and obtain efficiency of 17% for 30 cm 2 devices.